Les fleuves dans le projet urbain : entre risque et identité paysagère - Léa Assouline (Projets de Paysage)
This article studies rivers in urban planning projects with a focus on the notions of risk and identity. Research on sustainable development, resilience, and landscape planning then leads to devising the notion of a synergy between risk and identity in innovative projects and new modes of governance. It pleads in favour of landscape planning from a global and project-oriented perspective, revealing the positive value of risk as a defining element in the identity of a place through the notion of risk culture.